Advanced cutaneous squamous cell carcinoma of the head in two renal transplanted patients treated with cemiplimab. (2nd December 2021) - Orte Cano, C.; Van Meerhaeghe, T.; Tannous, J.; Lienard, D.; Van Gestel, D.; Cuylits, N.; Luce, S.; Carlot, S.; Le Moine, A.; Aspeslagh, S.; del Marmol, V.
Abstract: It is well known that organ transplant recipients are prone to develop non‐melanoma skin cancers, particularly cutaneous squamous cell carcinoma (cSCC). This is explained by the long‐term use of immunosuppressants and thus the decrease of the immunosurveillance that protects from developing malignant tumours. Solid organ transplant recipients (SOTRs) are 65–250 times more likely to develop cSCC compared to the general population (Am J Transplant 2017; 17: 2509). Moreover, in these patients cSCCs follow a more aggressive course. Close follow‐up and regular skin check‐ups by a dermatologist are, therefore, crucial in the management of these patients. When detected early, cSCC can be easily and effectively treated by a simple excision. However, when advanced, outcomes are poor. Immune checkpoints inhibitors (ICIs) have been recently added to our arsenal and represent a breakthrough, having proved to be effective in achieving long‐term responses. We, hereby, present two cases of difficult‐to‐treat cSCCs in renal transplanted patients.